A neutral polydisulfide containing Gd(III) DOTA monoamide as a redox‐sensitive biodegradable macromolecular MRI contrast agent. (27th July 2015) - Ye, Zhen; Zhou, Zhuxian; Ayat, Nadia; Wu, Xueming; Jin, Erlei; Shi, Xiaoyue; Lu, Zheng‐Rong
Abstract : This work aims to develop safe and effective gadolinium (III)‐based biodegradable macromolecular MRI contrast agents for blood pool and cancer imaging. A neutral polydisulfide containing macrocyclic Gd‐DOTA monoamide (GOLS) was synthesized and characterized. In addition to studying the in vitro degradation of GOLS, its kinetic stability was also investigated in an in vivo model. The efficacy of GOLS for contrast‐enhanced MRI was examined with female BALB/c mice bearing 4T1 breast cancer xenografts. The pharmacokinetics, biodistribution, and metabolism of GOLS were also determined in mice. GOLS has an apparent molecular weight of 23.0 kDa with T1 relaxivities of 7.20 mM −1 s −1 per Gd at 1.5 T, and 6.62 mM −1 s −1 at 7.0 T. GOLS had high kinetic inertness against transmetallation with Zn 2+ ions, and its polymer backbone was readily cleaved by L‐cysteine. The agent showed improved efficacy for blood pool and tumor MR imaging. The structural effect on biodistribution and in vivo chelation stability was assessed by comparing GOLS with Gd(HP‐DO3A), a negatively charged polydisulfide containing Gd‐DOTA monoamide GODC, and a polydisulfide containing Gd‐DTPA‐bisamide (GDCC). GOLS showed high in vivo chelation stability and minimal tissue deposition of gadolinium. The biodegradable macromolecular contrast agent GOLS is a promising polymeric contrast agent for clinical MR cardiovascular imaging and cancer imaging. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A neutral polydisulfide containing macrocyclic Gd‐DOTA monoamide (GOLS) was synthesized to optimize pharmacokinetic properties of biodegradable macromolecular MRI contrast agent. GOLS has shown high chelation stability against transmetallation in vitro and in vivo and improved minimal tissue deposition of gadolinium. It produces robust blood pool and tumor enhancement in MRI.